Educational Research in Educational Practice: Predictors of Use - Lysenko, Larysa V.; Abrami, Philip C.; Bernard, Robert M; Dagenais, Christian; Janosz, Michel (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
This study investigates the predictors of school practitioners’ (N = 2,425) use of educational research. The suggested model explained significantly but modestly the infrequent use of educational research by practitioners. Of the four factors in the study, “opinions about research” had the most explanatory power. The results are discussed in connection with existing knowledge about school practitioners’ use of educational research and implications for further research and practice.